1,3-Bis[(3-chloropyrazin-2-yl)oxy]benzene - Srinivasan, Thothadri (International Union of Crystallography, 2013)
The asymmetric unit of the title compound, C(14)H(8)Cl(2)N(4)O(2), contains one half-molecule, the complete molecule being generated by the operation of a twofold rotation axis. The Cl atom deviates significantly from the plane of the pyrazine ring [0.0215 (4) Å]. The central benzene ring makes a dihedral angle of 72.82 (7)° with the plane of the pyrazine ring.